2014
DOI: 10.1186/1743-7075-11-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gastrointestinal motility on obesity

Abstract: BackgroundChanges of gastrointestinal motility, which are important related to the food digestion and absorption in the gastrointestinal tract, may be one of the factors in obesity-formation.AimsThe changes of gastrointestinal motility were explored in the rats from diet-induced obesity (DIO), diet-induced obese resistant (DR) or control (CON) by diet intervention.MethodsAfter fed with a high fat diet (HFD), 100 male Sprague–Dawley rats were divided into DIO, DR and CON groups. The rats from DIO and DR groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 41 publications
(44 reference statements)
1
23
1
2
Order By: Relevance
“…Previous studies showed that the absorption of nutrients occurs mostly in the proximal intestine, and few nutrients reach the ileum [ 33 ]. Furthermore, a HFD reduces the motility of the duodenum [ 34 ]. This decrease in motility may have been sustained by the increase in the density of (inhibitory) nitrergic neurons in the present study (Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the absorption of nutrients occurs mostly in the proximal intestine, and few nutrients reach the ileum [ 33 ]. Furthermore, a HFD reduces the motility of the duodenum [ 34 ]. This decrease in motility may have been sustained by the increase in the density of (inhibitory) nitrergic neurons in the present study (Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, loss of ICCs and disruption to their networks are likely to play an important role in various gastrointestinal motility disorders in patients and animal models[ 11 ]. As a receptor tyrosine kinase, c-kit was used as a marker of ICC[ 19 ]. In this study, the protein and gene expression levels of c-Kit and SCF in the smooth muscle layers of gastric antrum and corpus were examined using western blotting and RT-PCR analyses.…”
Section: Resultsmentioning
confidence: 99%
“…[ 15 , 18 ] Furthermore, c-kit is considered to be a marker to identify ICCs, as a previous study demonstrated that ICCs express c-kit and that all c-kit cells expressed by GIT are ICCs. [ 19 ]…”
Section: Introductionmentioning
confidence: 99%
“…The endpoint of phenol red transit in small intestine was visualized by adding a few drops of 0.5 M sodium hydroxide. The intestinal transit for each rat was determined by the following formula 31 :…”
Section: Measurements After Euthanasiamentioning
confidence: 99%